2016
DOI: 10.1186/s40064-016-2188-3
|View full text |Cite
|
Sign up to set email alerts
|

The bizzare phenomenon of smokers’ paradox in the immediate outcome post acute myocardial infarction: an insight into the Malaysian National Cardiovascular Database-Acute Coronary Syndrome (NCVD-ACS) registry year 2006–2013

Abstract: Background‘Smoker’s paradox’ is a controversial phenomenon of an unexpected favourable outcome of smokers post acute myocardial infarction. There are conflicting evidences from the literature so far. We investigate for the existence of this phenomenon in our post acute myocardial infarction patients.Methods We analysed 12,442 active smokers and 10,666 never-smokers diagnosed with STEMI and NSTEMI from the Malaysian National Cardiovascular Database-Acute Coronary Syndrome (NCVD-ACS) year 2006–2013 from 18 hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
7
25
0
1
Order By: Relevance
“…This is supported by the National Health and Morbidity Survey Malaysia which stated that the Malaysian population has a higher prevalence of smoking with the prevalence of adult male smokers being 46.5%. 25 , 26 This is consistent with the NCVD database registry annual reports. 12 Moreover, a high prevalence of smoking (48.7%) and hypertension (31.7%) among male residents in rural Selangor, Malaysia were found in another study.…”
Section: Discussionsupporting
confidence: 88%
“…This is supported by the National Health and Morbidity Survey Malaysia which stated that the Malaysian population has a higher prevalence of smoking with the prevalence of adult male smokers being 46.5%. 25 , 26 This is consistent with the NCVD database registry annual reports. 12 Moreover, a high prevalence of smoking (48.7%) and hypertension (31.7%) among male residents in rural Selangor, Malaysia were found in another study.…”
Section: Discussionsupporting
confidence: 88%
“…The other interesting nding of the present study was former smoker closely linked to good responder of stem cell therapy in the EnD-CAD patients. This association was compatible with the previous misleading phenomenon of "smoker's paradox" [33,34], indicating better clinical outcomes were observed among the smokers suffering from acute myocardial infarction. Recent clinical researches [35,36] have debunked that bizarre "smoker's paradox" was mainly affected by age factor because the majority of smokers presenting to hospital were ten years younger than nonsmokers.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, this can be attributed to the low atherosclerotic risk profile of the smoker group with relatively younger age, lesser prevalence of diabetes and hypertension, and less severe coronary anatomy (MVD). It has been reported that with an appropriate adjustment of these confounding factors, the dubious benefit of smoking diminishes [12], and studies have reported poor postecoronary revascularization follow-up in smokers [12,18,25,28,30].…”
Section: Multivessel Diseasementioning
confidence: 99%